Genetic analysis for seed yield and its contributing traits in Indian mustard [(Brassica juncea (L.) Czern and Coss)]: Genetic analysis for seed yield and its contributing traits in Indian mustard [(Brassica juncea (L.) Czern and Coss)] - MAHAK SINGH; RUPENDRA SINGH; KULDEEP YADAV; JAGDISH PRASAD CHAURASIYA (Journal of Oilseeds Research, 2020)
Highly significant differences were recorded, majority of the characters except number of primary branches/plant, among the 28 genotypes of Indian mustard tested. Parent’s vs F1’s for all the characters revealed significant differences. The estimates of all genetic components were found highly significant for days to 50% flowering, days to maturity, plant height, main raceme length, number of siliquae/plant, number of primary branches/plant, number of secondary branches/plant, oil content, 1000-seed weight and seed yield/plant. The estimates of mean degree of dominance were more than unity for number of secondary branches/plant, 1000-seed weight, oil content and seed yield/plant. The proportion of genes with positive and negative effects was near or equal to theoretical value for all characters except seed yield/plant.